Anaphylactic shock induced by intravenous ketorolac: A case report - Huijuan Lu; Kaili Lai; Shuzhu Lin; Guining Dang (Heliyon)
Ketorolac trometamol injection is the first injectable nonsteroidal anti-inflammatory drug (NSAID) approved for the short-term management of moderate to severe pain. As a non-opioid alternative, it represents a critical development for acute pain relief, particularly in postoperative and injury-related scenarios. Like other NSAIDs, ketorolac trometamol is associated with common adverse reactions such as dizziness, headache, drowsiness, nausea, and vomiting, which are generally mild to moderate. However, rare but severe reactions like anaphylactic shock have been reported. This case report highlights a specific instance of anaphylactic shock induced by intravenous ketorolac trometamol, emphasizing the rapid onset of symptoms and the importance of vigilant monitoring during administration to prevent severe outcomes. Additionally, recommendations for post-recovery monitoring and allergological evaluation are provided to enhance clinical management in similar cases.